A Multi Waveform Adaptive Driving Scheme for Reducing Hysteresis Effect of Electrowetting Displays - Li, Wei; Wang, Li; Henzen, Alex (Frontiers in Physics, 2020)
Electrowetting display (EWD) is a new reflective display technology, which has the advantages of ultra-low power consumption, high contrast, fast response and full-color. However, due to a hysteresis effect, accurate gray scale display of EWDs cannot be achieved, which seriously restricted the display effect and performance of EWDs. In order to reduce the influence of hysteresis effect, a multi waveform adaptive driving scheme was proposed in this paper. Firstly, a multi waveform driving system was designed and implemented by a STM32 master chip and an AD5304 driver chip. The driving system could automatically select different driving waveforms according to the preset switching conditions. Then, different driving waveforms were designed and implemented according to different driving stages of EWDs. Finally, driving waveforms were mapped with each stage of the driving process one by one to realize the adaptive driving of multiple waveforms. The experimental results showed that, compared with the conventional square wave, the maximum hysteresis difference of hysteresis curve could be reduced by 39.19% with the multi waveform driving scheme.